Find all School-related info fast with the new School-Specific MBA Forum

It is currently 31 Aug 2016, 01:47
GMAT Club Tests

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

If xy + z = x(y+z), which of the following must be true? A.

  post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
Manager
Manager
User avatar
Joined: 21 Sep 2006
Posts: 111
Location: Where you mind is
Followers: 1

Kudos [?]: 18 [0], given: 0

If xy + z = x(y+z), which of the following must be true? A. [#permalink]

Show Tags

New post 23 Dec 2007, 21:47
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

If xy + z = x(y+z), which of the following must be true?

A. x = 0, z = 0
B. x = 1, y = 1
C. y = 1, z = 0
D. x = 1, y = 0
E. x = 1, z = 0

What I did was:

Step 1: xy + z = xy + xz

Step 2: Substitute the values in the answer options to see which one gives equal values. But the problem was, i found 3 such answers!

B: 1 + z = 1 + z
D: z = z
E: y = y

The OA is E. Can you guys please help to explain this?

Thanks.
Manager
Manager
avatar
Joined: 01 Sep 2007
Posts: 100
Location: Astana
Followers: 1

Kudos [?]: 23 [0], given: 0

 [#permalink]

Show Tags

New post 23 Dec 2007, 21:53
hi there

xy+z=xy+xz =>

z = xz

z- xz=0
z(1-x)=0
z=0, x=1
SVP
SVP
avatar
Joined: 28 Dec 2005
Posts: 1575
Followers: 3

Kudos [?]: 130 [0], given: 2

 [#permalink]

Show Tags

New post 25 Dec 2007, 10:16
expand and rearranging the given equation gives you:

xy-xy+z-xz=0
z-xz=0
z(1-x)=0

the only way for that to be true is for one of the terms to be zero, namely, either z=0 or 1-x=0, i.e. x=1.

Option E states this
  [#permalink] 25 Dec 2007, 10:16
Display posts from previous: Sort by

If xy + z = x(y+z), which of the following must be true? A.

  post reply Question banks Downloads My Bookmarks Reviews Important topics  


GMAT Club MBA Forum Home| About| Terms and Conditions| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group and phpBB SEO

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.